The career planning of young prisoner study at Lembaga Pembinaan Khusus Anak (LPKA) Tanjung Pati - Elviana Elviana; Afdal Afdal; A. Muri Yusuf (Fakultas Ilmu Pendidikan UNP)
One of the tasks of development that must be traversed by a teenager is a task in planning or choosinga career/job for the future. However, many conditions faced by teens who were in Lembaga Pembinaan Khusus Anak (LPKA) as the Special Children's Mentoring Institute,include the lack of career information that they have caused them difficulty and have trouble doing career planning for their future. This research aims to describe of the problem of young prisoner in the career planning process. This research used quantitative approaches with descriptive-quantitative method. The sample in this research consisted of 32 young prisoner. The results showed that young prisoner who have problems of planning a career on the very high category as many as 17 people with 51.51%, in high category as many as 11 people with 33.33% and on the category quite as many as 4 people with 12.12%.